Grammatical Error Detection in Automatic Essay Scoring and Feedback - Gamon, Michael; Chodorow, Martin; Leacock, Claudia; Tetreault, Joel (Handbook of Automated Essay Evaluation, 2013)
In English-language essay scoring guides, such as the Test of English as a Foreign Language (TOEFL) or Graduate Record Examination (GRE), control of language is an important part of the rubric. Essay scoring rubrics include control of language as one of the criteria for a high-scoring essay and lack of control of language as a criterion for a low-scoring essay. For example, at the highest score point of 6, a TOEFL essay “displays consistent ability in the use of language.” A mid-range essay, with a score of 3, may reveal one of the following weaknesses: “a noticeably improper choice of words or word forms” or “numerous errors in sentence structure and/or usage.” A poor essay, with the lowest score of 1, “may contain severe and persistent writing errors.” 1 This chapter is based on the assumption that the absence of grammatical errors in an essay, that is, correct usage and syntax, is a clear marker of a student’s control of the English language. Thus, when a scoring engine can identify grammatical errors, these errors can be used as a feature to help determine an essay’s score.